Psychological and pedagogical support of agricultural college students learning - M. Kashapov; T. Ledovskaya (Trakia Journal of Sciences)
The purpose of the research is depicting study progress of agricultural college students with different individual and typological peculiarities. The following methods were used for diagnostics: 1) study progress parameters were defined with the help of: a) «Complex diagnostics of students’ preparedness for learning at a college» method (structural parameter); 2) qualitative analysis of academic progress during the assessment period (effectiveness parameter). The article states that individual and typological peculiarities of college students provide for characteristics of their study progress and preparedness for learning at a college. In the course of research, two parameters of study progress of first-year students were defined: structural parameter of study progress (developed psychological structure of learning activity) and effectiveness parameter of study progress (academic progress level). The article proves a certain interrelation between individual and typological peculiarities and good academic progress. Students with different individual and typological peculiarities have various levels of structural and effectiveness parameters of good academic progress: introverts tend to be more successful than extroverts. Considerable differences in the organization of individual psychological structure of students’ learning activity are shown. The research results will be useful for sorting out psychological types of students in order to provide for individualization and differentiation of higher education. The article gives basic recommendations on considering individual and typological peculiarities of agricultural college students in the process of learning.